1861 N.C. Sess. Laws 25 - (:unkn) unknown (My University, 1861)
Pub. Laws, 2d. Extra Sess., ch. 17, § 10: Every resident enrolled and notified, as is directed in the third section of this act, shall within one month thereafter, provide himself with a good musket, smooth bore gun or rifle, shot pouch and powder horn, and shall appear so armed and accoutred when called out to exercise or in actual service; the commissioned officers shall severally be armed with a sword or revolver at his discretion
Keywords: ARMED FORCES